2013
DOI: 10.1186/1477-7819-11-61
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes in patients with small cell lung cancer: comparative analysis of computed tomograpy-detected patients with others

Abstract: BackgroundIt is shown that low-dose computed tomography (CT) screening is useful for a reduction in lung-cancer-specific mortality in heavy smokers. However, the information about effectiveness according to the histological types of lung cancer has not been adequately investigated especially small cell lung cancer (SCLC). The present study was performed to see the clinical benefit of CT screening in patients with SCLC following thoracotomy.MethodsWe retrospectively reviewed the outcome in patients with early s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, this conclusion may differ among different studies. Jie et al ( 3 ) also reported that the IC group had a lower rate of distant metastasis by 8% (95% CI: 1–16, P=0.02). Furthermore, a randomized phase 3 trial ( 37 ) divided patients into two groups, one receiving IC followed by concurrent chemoradiotherapy (n=70), and the other receiving concurrent chemoradiotherapy alone (n=75); finally, 5 (7%) patients in the induction group and 8 (11%) in the concurrent chemoradiotherapy group developed distant metastasis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, this conclusion may differ among different studies. Jie et al ( 3 ) also reported that the IC group had a lower rate of distant metastasis by 8% (95% CI: 1–16, P=0.02). Furthermore, a randomized phase 3 trial ( 37 ) divided patients into two groups, one receiving IC followed by concurrent chemoradiotherapy (n=70), and the other receiving concurrent chemoradiotherapy alone (n=75); finally, 5 (7%) patients in the induction group and 8 (11%) in the concurrent chemoradiotherapy group developed distant metastasis.…”
Section: Discussionmentioning
confidence: 92%
“…Induction chemotherapy (IC) is considered as a reliable approach to controlling locally advanced LC, increasing the rate of laryngeal preservation and decreasing the risk of local spread or distant metastasis, thereby increasing the therapeutic efficacy. However, locoregional control must be performed in accordance with the tumor borders following IC, which should be marked at the start of the therapy ( 3 ), regardless of the response to IC. The clinical value of IC remains a matter of debate, particularly in cases with resectable advanced LC.…”
Section: Introductionmentioning
confidence: 99%
“…While other studies have suggested that the poor efficacy of current treatment options for disease progression is related to the lack of benefit of early diagnosis, as such subjects do not usually have the option of surgery, as systemic spread and paraneoplastic syndrome typically impede the therapeutic potential of resection (32). Improved or favorable survival rates in patients with resected SCLC have been described in recent retrospective analyses (33,34), indicating that surgery is associated with improved survival for certain patients with early-stage SCLC (35). The results of the present study are almost identical to that of these previous studies (36).…”
Section: Discussionmentioning
confidence: 99%
“…According to National Comprehensive Cancer Network (NCCN) guidelines, surgery is only recommended in patients with stage I–IIA (T1–2, N0, M0) SCLC after standard clinical staging evaluation. These patients without lymph node involvement can benefit from surgical resection, which is associated with a median survival of 35–79 months [ 5 10 ]. Surgery with adjuvant chemotherapy can also improve long-term survival compared to concurrent chemoradiation.…”
Section: Introductionmentioning
confidence: 99%